Resistance to fungal diseases - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
In 1984, most of the pathology efforts of the CIAT Bean Program concentrated on the evaluation of bean germplasm for their reaction to the main bean pathogens under field conditions in several international nurseries throughout many of the bean growing areas. High priority was given to the most widespread and economically important bean diseases such as anthracnose, rust, angular leaf spot, and web blight. In addition to the international bean disease nurseries, other bean program germplasm and breeding progenies were routinely evaluated either in specific breeding projects or in advanced nurseries both in Colombia and other areas of Latin America in close collaboration with bean scientists from national programs. Similarly, bean germplasm accessions and lines were evaluated in the greenhouse for their reaction to rust, anthracnose, angular leaf spot, halo blight, and common bacterial blight to study the pathogenic variation existing among the populations of bean pathogens, disease resistance mechanisms, and basic studies in bean pathology. (CIAT)